1901-02 Va. Acts 526, ch. 467, § 35, pt. 8 - (:unkn) unknown (My University, 1902)
To direct the location of all building for storing gunpowder, fire-crackers, or other fireworks manufactured or prepared therefrom, kerosene oil, nitroglycerine, camphene, burning fluid, or other combustible material; to regulate the exhibition of fireworks, the discharge of fire-arms, the use of candles and lights in barns, stables, or other buildings, and to regulate or restrain the making of bonfires in streets and yards.
Keywords: DISCHARGE; GUNPOWDER - STORAGE